2016
DOI: 10.5713/ajas.15.0013
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of L-Threonine for Optimization of Dietary Crude Protein Levels in Broilers

Abstract: This study was conducted to evaluate the performance of broiler chickens fed low protein diets supplemented with L-threonine. Four hundred and sixty two 1-day-old broiler chicks were randomly allotted to seven treatments with six replicates each and eleven chicks per replicate. Seven treatments included; T1-control, T2, T4, T6-without L-threonine and T3, T5 ,T7-with L-threonine supplementation with a CP reduction by 0.75, 1.50 and 2.25 per cent units, respectively. Feed was offered in pre-starter (0-14 days), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Traditionally, they've been utilized to enhance plant growth (van Rensburg, 2015). Additionally, humic acids, derived from decomposed organic matter in soil and lignite (MacCarthy, 2001), are being explored as potential alternatives to antibiotics in poultry diets (Nagaraju et al, 2014). Humic substances exhibit promising potential in bolstering gastrointestinal health, leading to improved body weight, feed conversion, and immune response (Taklimi et al, 2012;Ozturk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, they've been utilized to enhance plant growth (van Rensburg, 2015). Additionally, humic acids, derived from decomposed organic matter in soil and lignite (MacCarthy, 2001), are being explored as potential alternatives to antibiotics in poultry diets (Nagaraju et al, 2014). Humic substances exhibit promising potential in bolstering gastrointestinal health, leading to improved body weight, feed conversion, and immune response (Taklimi et al, 2012;Ozturk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Research by Arif et al (2016) demonstrated significant enhancements in broiler BWG and FCR with HA supplementation. Moreover, studies by Nagaraju et al (2014) revealed that incorporating HA into broiler diets enhances meat quality, BWG, and immune function. Ozturk et al (2010) further reported improvements in growth, carcass characteristics, blood parameters, and gastrointestinal health with HA supplementation.…”
Section: Introductionmentioning
confidence: 99%